Vaccination With Mouse Dendritic Cells Loaded With an IpaD-IpaB Fusion Provides Protection Against Shigellosis - Arizmendi, Olivia; Kumar, Prashant; Zheng, Qi; Stewart, Jason P.; Picking, William D.; Picking, Wendy; Martinez-Becerra, Francisco J. (Frontiers in Immunology, 2019)
Diarrheal diseases are a major cause of morbidity and mortality worldwide. They are most prevalent in settings with inadequate sanitation, poor hygiene and contaminated water. An important diarrheal pathogen in such settings is Shigella. No commercially available vaccine exists against shigellosis and immunity to the pathogen is serotype-restricted. We have previously shown that a polypeptide fusion of the Type Three Secretion Apparatus (T3SA) proteins IpaB and IpaD (named DBF) was efficacious as a vaccine against Shigella. Vaccination using different administration routes indicated that protection conferred by this vaccine did not fully correlate with antibodies. To define the immune responses involved in protection, we studied cellular responses to intranasal immunization with the DBF fusion and the adjuvant dmLT. We found dendritic cell (DC) activation at the nasal associated lymphoid tissue (NALT). Activation markers CD86 and MHCII significantly increase in cells from immunized mice. Antigen exposure in vitro further confirmed the upregulation of CD80 and CD40 in primary dendritic cells. Animals immunized with antigen-primed dendritic cells were protected against Shigella infection, at levels comparable to the efficacy of immunization with the protein vaccine formulation. Therefore, we show that DCs are enough to provide immunity, and propose a mechanism of protection against Shigella spp. based on DC-mediated antigen presentation to T cells.